A Calcium Enterolith in a Patient with Crohn’s Disease and Its In Vitro Dissolubility in Citric Acid - Masaya Iwamuro; Haruo Urata; Sakiko Hiraoka; Masayasu Ohmori; Yoshitaka Kondo; Yoshiro Kawahara; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
The microstructure and dissolubility of a calcified enterolith and enterolith pieces removed from a 26-year-old Japanese woman with Crohn’s disease were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy. The enterolith showed a multilayered structure with fatty acid calcium and magnesium phosphate. The amount of calcium, magnesium, and phosphate decreased after they were immersed in a citric acid solution, suggesting a potential contribution of acidic aqueous solution to elute inorganic substances contained in calcified enteroliths. This is the first study to investigate the in vitro dissolubility of calcified enteroliths induced by citric acid solution.